Characterization and Properties of Copper and Carbon Powders Mixture - Mazlan, Azri Izwan (Universiti Teknologi Petronas, 2008)
Powder metallurgy (P/M) is one of a metal fabrication teclmique which involves three main stages, i.e. mixing, compaction and sintering. The P/M teclmique allows the blending or mixing of additives (carbon) to the base powder (copper) prior to compacting and sintering of parts. The additives will enhance certain property of a metal. The objective of this project is to study the homogeneity of the mixture, the compressibility of the mixture, and the properties of the sintered mixture (copper and carbon). Experiment will be conducted to analyze the characterization and properties of the new metal produce. The copper and graphite powder are used to produce this mixture. The graphite powders have been grind using mortar grinder to become smaller particles. The copper and the graphite powder have been mixed based on weight fraction (98.5wt% Copper and 1.5wt% Carbon). It is compacted using autoPallet press machine and sintered by using furnace. Microscopic analyses using SEM have been done on the powder, mixing mixture, compacted pallet and also sintered pallet. The powder mixture was found homogeneous. The highest densities of green and sintered were 6.66 g/cm' and 7.28 g/cm' respectively. The highest hardness of the Cu- C mixture was 27.5 HV.